2022
DOI: 10.3389/fmicb.2022.918262
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Converting Keratin-Containing Wastes Into Biofertilizers for Sustainable Agriculture

Abstract: Keratin-containing wastes become pollution to the environment if they are not treated properly. On the other hand, these wastes can be converted into value-added products applicable to many fields. Organic fertilizers and biofertilizers are important for sustainable agriculture by providing nutrients to enhance the growth speed of the plant and production. Keratin-containing wastes, therefore, will be an important resource to produce organic fertilizers. Many microorganisms exhibit capabilities to degrade kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 171 publications
0
8
0
Order By: Relevance
“…Feathers, which are the primary byproduct of poultry processing, contain a high proportion of proteins (≥90%), including essential amino acids, making them a valuable source of nutrition. , However, feather keratin, which is a particularly resistant protein, is often disposed of in an unregulated manner, leading to environmental pollution and limiting its potential applications. , Therefore, there is an urgent need to develop environmentally friendly and cost-effective strategies to exploit the high value-added products of feather keratin. Recent studies have shown that hydrolysate peptides derived from feather keratin (FKHPs) possess significant antioxidant activity, as demonstrated by their excellent DPPH and ABTS radical scavenging capacities, as well as their ability to scavenge intracellular ROS. These peptides are also rich in hydrophobic amino acids, which are a characteristic component of uric acid-lowering peptides that have been previously identified, including XOD inhibitory peptides. ,, Thus, we hypothesize that FKHPs may be an ideal source of uric acid-lowering peptides, yet to date, no XOD inhibitory peptides have been identified from FKHPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feathers, which are the primary byproduct of poultry processing, contain a high proportion of proteins (≥90%), including essential amino acids, making them a valuable source of nutrition. , However, feather keratin, which is a particularly resistant protein, is often disposed of in an unregulated manner, leading to environmental pollution and limiting its potential applications. , Therefore, there is an urgent need to develop environmentally friendly and cost-effective strategies to exploit the high value-added products of feather keratin. Recent studies have shown that hydrolysate peptides derived from feather keratin (FKHPs) possess significant antioxidant activity, as demonstrated by their excellent DPPH and ABTS radical scavenging capacities, as well as their ability to scavenge intracellular ROS. These peptides are also rich in hydrophobic amino acids, which are a characteristic component of uric acid-lowering peptides that have been previously identified, including XOD inhibitory peptides. ,, Thus, we hypothesize that FKHPs may be an ideal source of uric acid-lowering peptides, yet to date, no XOD inhibitory peptides have been identified from FKHPs.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, feather keratin, which is a particularly resistant protein, is often disposed of in an unregulated manner, leading to environmental pollution and limiting its potential applications. 19,20 Therefore, there is an urgent need to develop environmentally friendly and cost-effective strategies to exploit the high value-added products of feather keratin. Recent studies have shown that hydrolysate peptides derived from feather keratin (FKHPs) possess significant antioxidant activity, as demonstrated by their excellent DPPH and ABTS radical scavenging capacities, as well as their ability to scavenge intracellular ROS.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on this, keratin-based biofilms have great potential for conversion into biofertilisers. These biofertilisers not only provide nutrition to the land, in order to improve the growth rate and yield of plants but also can reduce the soil damage caused by the application of artificial chemicals and excessive chemical fertilisers [ 143 ]. The high biodegradability of keratin-based biofilms opens up a new direction for the manufacture of environmentally friendly and nutritional mulch films in ecological agriculture [ 144 ].…”
Section: Functional Properties Of Keratin-based Filmsmentioning
confidence: 99%
“…Keratin is a material abundant in nature and is a primary component of animal feathers, nails, horns, and surface epithelium. 21 Keratin is biocompatible and biodegradable, making it highly promising in the synthesis of polymer materials. 22 This is mainly due to the side chains of the amino acids in the keratin peptides possessing unique chemical configurations, bonding capabilities, charges, and reactivities.…”
Section: Introductionmentioning
confidence: 99%